Surveillance radars onboard stratospheric platform systems (SPS) for ship tracking - Stojce Ilcev, Dimov (International Journal of Engineering and Technology, 2018)
In this article is proposed and described new solution for ship tracking via surveillance radars onboard of Stratospheric Platform Sys-tems (SPS) or as known as High Altitude Platforms (HAP). Such tracking system has significant competitive edge in contrast to the surveillance radar at shore or onboard ships, aircraft and spacecraft. The idea and proposal of employing Tracking Surveillance Radars (TSR) onboard SPS is novel and very cost effective as well. Such a system is suitable to be implemented for control of maritime traffic and tracking of ships at sea, approaching to the anchorage, in passages and in coastal waters where must be provided higher security and safety conditions. The TSR system works very similar as radar installed onshore and used for observation and controlling certain part of sea areas for seagoing ships or air space for aircraft. The new proposal of possible placing of TSR onboard three SPS stations between Grate Britain and Ireland islands is presented as well. Â Â